2021
DOI: 10.1021/acs.energyfuels.1c01361
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient of Gas in Shale Reservoirs and Insights into Its Diffusion Behavior: A Modeling and Experimental Study

Abstract: Diffusion plays an important role in gas production from a shale matrix. To determine the gas diffusion mechanism in micro-/nanopores and to tackle the difficult problem of the quantitative description of the gas diffusion capacity in shale reservoirs, a differential momentum equation considering fluid viscosity is derived, and an apparent diffusion coefficient model considering shale porosity, tortuosity, and Knudsen number is built. The diffusion ability testing experiment carried out to verify the reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Self-absorption, water-rock chemistry occurs when shale is in contact with a liquid medium. , This can lead to changes in the water absorption and physical properties of the shale, the ionic concentration and chemical electrical properties of the liquid medium . This experiment explores the extent and changing patterns of such interactions through natural sorption measurements, ion diffusion measurements, and elemental geochemical measurements simulations.…”
Section: Experimental Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-absorption, water-rock chemistry occurs when shale is in contact with a liquid medium. , This can lead to changes in the water absorption and physical properties of the shale, the ionic concentration and chemical electrical properties of the liquid medium . This experiment explores the extent and changing patterns of such interactions through natural sorption measurements, ion diffusion measurements, and elemental geochemical measurements simulations.…”
Section: Experimental Researchmentioning
confidence: 99%
“…Currently, the studies for core experiments mainly focus on the comparison of self-absorption and backdriving, determination of mechanical properties, exploration of microstructure, and proppant reflux law. For example, Duan (2021) proposed a new diffusion model through the dual means of modeling and experimentation to achieve quantitative calculation of shale gas diffusion flow under given reservoir conditions, which meets the needs of engineering to accurately adjust the production system . Chen (2018) demonstrated that gypsum crystallization during shale–fluid reaction can induce fracturing to increase production by means of chemical experiments, and found that mineral crystallization or growth-induced spontaneous microfracture extension effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11−13 Duan et al experimentally found that the apparent diffusion coefficient is positively correlated with the pore size but negatively correlated with pressure. 14 Lu et al carried out low-field NMR experiments on shale samples and found that CO 2 exhibits stronger adsorption ability than CH 4 . They also claimed that the methane displacement efficiency by CO 2 is mainly affected by a competitive adsorption effect and the reduction of CH 4 partial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the adsorbed gas could take up 20–85% of the total gas-in-place (GIP) in the shale matrix. , Therefore, the gas adsorption and transport behaviors play crucial roles in accurately predicting the potential of shale gas exploration and CO 2 sequestration in shale reservoirs. So far, extensive efforts have been devoted to understanding the gas adsorption and transport characteristics in shale reservoirs. Duan et al experimentally found that the apparent diffusion coefficient is positively correlated with the pore size but negatively correlated with pressure . Lu et al carried out low-field NMR experiments on shale samples and found that CO 2 exhibits stronger adsorption ability than CH 4 .…”
Section: Introductionmentioning
confidence: 99%